2019
DOI: 10.3389/fpsyt.2019.00695
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Profile in Ultra High Risk for Psychosis and Schizophrenia: A Comparison Using Coordinated Norms

Abstract: Background: Cognitive impairment is not only a core aspect of schizophrenia but also commonly observed in help-seeking youth at ultra high risk for psychosis (UHR), with potential implications for prognosis and individualized treatment. However, there is no consensus on the cognitive profile in the UHR state, partly due to lack of valid comparisons of performance in established schizophrenia and UHR. Objectives: To compare the cognitive functioning and profile of UHR subjects to a sample with schizophrenia, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 54 publications
1
16
0
Order By: Relevance
“…54 One possible marker of this change in development would be intellectual functioning, which can be reduced in these patients. 55,56 General cognition is impaired in individuals who later develop SZ even before the FEP, [57][58][59] resulting in consistent IQ deficits. 60,61 A previous study 55 and metaanalysis 62 found that the risk of developing SZ increases approximately 3.8% per 1-point decrease in IQ.…”
Section: Cognitive Trajectoriesmentioning
confidence: 99%
“…54 One possible marker of this change in development would be intellectual functioning, which can be reduced in these patients. 55,56 General cognition is impaired in individuals who later develop SZ even before the FEP, [57][58][59] resulting in consistent IQ deficits. 60,61 A previous study 55 and metaanalysis 62 found that the risk of developing SZ increases approximately 3.8% per 1-point decrease in IQ.…”
Section: Cognitive Trajectoriesmentioning
confidence: 99%
“…The course of schizophrenic disorders can be continuous or episodic, with progressive or permanent cognitive deficits [14]. The first phase (although different in both genders in terms of anatomical differences in the white matter of the brain) is similar in most patients and is characterized by prodromal symptoms: Anxiety, irritability, social withdrawal, and depressed mood [15,16]. Recent evidence-based data also indicate a strong association between schizophrenia and bipolar disorder (BD) through a clear relationship between mitochondrial genes in both diseases [17].…”
mentioning
confidence: 99%
“…Our F20 group represents a mix of recently diagnosed individuals, some medication naïve, and others with a longer duration of illness. It is possible that a greater amount of change happened in the former subgroup, as indicated by our previous study ( Anda et al, 2019 ), and that cognitive recovery from an acute psychotic episode is more likely to happen during early psychotic episodes regardless of diagnosis. It might also be argued that although the between-group difference was about 10% away from statistical significance, it still represents a clinically meaningful difference.…”
Section: Discussionmentioning
confidence: 76%